Modelo de Priorización de Obras Geotécnicas para la Intervención y Mantenimiento de Obras de Infraestructura Vial del CONAVI - Calvo-Vargas, Gabriel Enrique (Instituto Tecnológico de Costa Rica, 2013)
The national road-network covers approximately 7429 kilometers of which are administered by Consejo Nacional de Vialidad (CONAVI). According to LANAMME studies approximately 58% of the national roads are in areas with geotechnical issues that could affect the state of them. Therefore CONAVI needs tools to help in planning tasks and maintenance of the road-network, so that, to ensure levels of safety, comfort and serviceability appropriate. The proposed model has its focus of study geotechnical infrastructures of the road-network without regarding other infrastructure components. This model aims to help in managing the priorities of the national road-network for optimizing the operation and maintenance of geotechnical issues. This model gathers nine criteria factors taking into account socio-economic, environmental and technical aspects. Through expert consultation, multi-criteria evaluation methods, databases from different sources and geographic information systems determines the proper order of priority As a case of study the model was applied to Oreamuno, Cartago zone. The outcome of the study was that, in general, the area has a medium susceptibility to geotechnical problems and the prioritization level of geotechnical aspects is moderate with some damages that need to be treated.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2013.
Keywords: SIG; Conservación; Evaluación multicriterio; Sistemas de información geográfica